Vues depuis Pékin, les actuelles évolutions du système portuaire de la RPC - Benjamin Claverie (L'Espace Politique)
Faced with a global port organization increasingly polycentric and having to face a deindustrialization sometimes difficult, Western ports have experienced a downgrading in the world port hierarchy, now largely dominated by East Asia and the People’s Republic of China in particular. By reading articles specializing in logistics issues published by Asian authors, processing statistics issued by the Chinese government and international institutions, and making a field visit to a Chinese dry port, the author analyzes the Chinese policy that has enabled the Chinese port system to develop, catch up and then become superior on a global scale. The article begins with an examination of developments in port planning, which have resulted in the decentralization of port management to the provincial and municipal levels, as well as the integration of ports into broader national planning issues. The second part is devoted to the comparative advantages of the various players in the Chinese port system, enabling them to project themselves globally within the framework of the Belt and Road Initiative.